Characteristic MR Imaging Features and Serial Changes in Adult-Onset Alexander Disease: A Case Report - Ha Yun Oh; Ra Gyoung Yoon; Ji Ye Lee; Ohyun Kwon; Woong-Woo Lee (Journal of the Korean Society of Radiology, 2023)
Adult-onset Alexander Disease (AOAD) is a rare genetically determined leukoencephalopathy that presents with ataxia, spastic paraparesis, or brain stem signs including speech abnormalities, swallowing difficulties, and frequent vomiting. The diagnosis of AOAD is frequently proposed based on the findings on MRI. We demonstrate two cases (37-year-old female and 61-year-old female) with characteristic imaging findings and changes in follow-up MRI in patients with AOAD, which were confirmed via glial fibrillary acidic protein (GFAP ) mutation analysis. On MRI, the typical tadpole-like brainstem atrophy and periventricular white matter abnormalities were noted. The presumptive diagnoses were made based on the typical MRI appearances and, subsequently, confirmed via GFAP mutation analysis. Follow-up MRI demonstrated the progression of atrophy in the medulla and upper cervical spinal cord. Our report could help raise awareness of characteristic MRI findings of AOAD, thus helping clinicians use GFAP analysis for AOAD diagnosis confirmation.